FACTORIAL STRUCTURE AND RELIABILITY OF A QUESTIONNAIRE ON LEARNING STRATEGIES IN UNIVERSITY STUDENTS: CEA-U - Martín Cabrera, Eduardo; García García, Luis Alberto; Torbay Betancor, Ángela; Rodríguez Blanco, Teresa (Anales de Psicología / Annals of Psychology, 2007)
The factorial structure and reliability of the Questionnaire of Learning Strategies in University Students (CEA-U) is analysed from the an-swers taken by 1105 students in the second cycle of a University Career. The questionnaire is formed into three stages: motivational, cognitive and metacognitive strategies, in which the exploratory factorial analysis throws light over eleven empiric factors. In a factorial analysis of Second Degree, the eleven factors group together into three macro factors or dimensions: one being Cognitive Dimension, which makes reference to the strategies employed for understanding the studied subject, the second being Organ-isational Dimension, which groups together the strategies of Organisation, Planning and Revision, and third and lastly An Approximate Dimension, which represents the motivational strategies that the student uses to ap-proach the study task. The First degree factors as well as the Second de-gree factors have high reliability indexes.